A test of the law of demand in a virtual world: exploring the Petri dish approach to social science - Edward Castronova (Center for Economic Studies and ifo Institute (CESifo), 2008)
We report results of an experiment on prices and demand in a fantasy-based virtual world. A virtual world is a persistent, synthetic, online environment that can be accessed by many users at the same time. Because most virtual worlds are built around a fantasy theme, complete with magic, monsters, and treasure, there is considerable skepticism that human behavior in such environments is in any way normal. Our world, Arden, was designed to test whether players in a typical fantasy environment were economically normal. Specifically, we tested whether fantasy gamers conform to the Law of Demand, which states that increasing the price of a good, all else equal, will reduce the quantity demanded. We created two exactly equivalent worlds, and randomly assigned players to one or the other. The only difference in the two worlds was that the price of a single good, a health potion, was twice as high in the experimental world than in the control. We allowed players (N = 43) to enter and play the environment for a month. We found that players in the experimental condition purchased 43.1 percent fewer of the potions, implying a demand elasticity of -0.431. This finding is well within the range one expects for normal economic agents. We take this as evidence that the Law of Demand holds in fantasy environments, which suggests in turn that fantasy gamers may well be economically normal. If so, it may be worthwhile to conduct controlled economic and social experiments in virtual worlds at greater scales of both population (thousands of users) and time (many months).
Keywords: C99; 330; Virtual worlds; experimental methods; Virtuelle Realität; Videospiel; Konsumentenverhalten; Mikroökonomische Konsumfunktion; Test